URGENSI BIMBINGAN KEAGAMAAN ISLAM TERHADAP PEMBENTUKAN KEIMANAN MUALAF - Anton Widodo (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
The Urgency of Islamic Religious Guidance Against the Formation of Faith This convert is an Islamic religious guide to the formation of converts' faith applied to converts who are problematic or not, because basically with the Islamic guidance Muslim converts will always remember Allah and be a straight way to reach a calmer and directed life. . Islamic religious guidance is done by lectures, religious discussions, and outpouring of the heart. In addition, there are daily programs such as congregational prayers, qiyamul lail material, there are also certain times such as the commemoration of Islamic holidays, Islamic studies with direct methods or indirect methods. The urgency of Islamic religious guidance is: First, it produces a change, improvement, and mental and mental hygiene which was initially still insecure so that the soul of the converts becomes calm and peaceful, behaves broadly, and to reach enlightenment the guidance of the Lord feels lighter. Second, to produce a change in courtesy that can benefit both yourself, the family environment, work environment and the social environment and the natural environment. Third, to produce social sensitivity in individuals so that tolerance and solidarity arise and develop, help and love. Social piety will make motivation to improve the antibody system from akhlaq al-madmumah so that ahkhlaq al-karimah is always maintained. Fourth, to produce spiritual intelligence in the individual so that a sense of desire arises to obey his Lord, sincerity in obeying all His commands and endurance to accept His test. The whole urgency and principle above is a means to improve the quality of the faith that grows and grows stronger, which originally will increase the taqlid faith into the faith of science so that it reaches the highest point, namely faith haq and essence.